Use of Aerial Photographs in Working Plans - Tomar, M. S. (Indian Forester, 1976)
Aerial photographs on 1 : 60,000 scale were used for stock-mapping during the preparation of Working Plan of Vidisha Forest Division. They proved very useful in correctly delimiting the boundaries of various forest types density and maturity classes as well as correction of block boundaries on maps with respect to topographic and drainage features. Preliminary interpretation of aerial photographs speeded the field work of stock-mapping by 1.6 times as compared to conventional method of stock-mapping. The speed of stock-mapping with aerial photographs was 26.7 compartments per man-month as against 17 with conventional method. The saving in time could more than compensate the cost involved in procuring aerial photographs, besides improving the accuracy of stock-maps. The use of aerial photographs would prove more economical if integrated surveys including forest inventory, erosion and site assessment survey, logging planning, etc. are alse contemplated simultaneously.